2016
DOI: 10.1007/s15010-016-0918-7
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous human alveolar echinococcosis in a Hungarian patient

Abstract: To our knowledge, this is the first confirmed autochthonous case of human alveolar echinococcosis in Hungary. To what extent diagnostic difficulties may contribute to underestimate this zoonosis in Eastern Europe is unknown. Differential diagnosis with alveolar echinococcosis should be considered for patients with multiple, tumor-like cystic lesions of the liver, in countries where this parasite is emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The first reported cases from neighbouring Belgium appeared nearly exclusively in Wallonia [ 55 , 56 ]. Also for the first time in Hungary, a case of AE was thought to be autochthonous in the south-west of the country [ 57 ]. Evidence of the disease was found for the first time in Poland and in five patients in north-eastern Romania by molecular genetic testing [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reported cases from neighbouring Belgium appeared nearly exclusively in Wallonia [ 55 , 56 ]. Also for the first time in Hungary, a case of AE was thought to be autochthonous in the south-west of the country [ 57 ]. Evidence of the disease was found for the first time in Poland and in five patients in north-eastern Romania by molecular genetic testing [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…No Czech cases were registered between 1998 and 2006, however 20 cases in the period of 2007–2014 [ 62 ]. We can assume the further spread of the disease from the first molecular genetic evidence for the existence of human AE in Romania, as well as the first autochthonous case from south-western Hungary [ 57 , 59 ]. Despite some high estimated figures of more than 1000 new cases annually [ 5 ], there is a distinct lack of data from Russia.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,41,42 In Europe, cases in the hitherto endemic area of Central Europe (France, Switzerland, Germany and Austria) are increasing in number. Moreover, the geographical distribution is expanding to countries previously considered AE-free like Poland, Slovakia, Hungary and the Baltic region, [43][44][45][46][47][48] challenging respective health care systems. 21 Key risk factors for acquiring AE in Europe are being a farmer, owning a dog or cat or having a kitchen garden.…”
Section: Key Pointmentioning
confidence: 99%
“…It is suggested that, due to this antigen, the metacestode of AE escapes the host immune response as shown in animal models [13][14][15] by modulating the T-cell response and activating a T-cell-independent B-cell reaction, which lacks antibody maturation. With conventional immunohistochemical staining of paraffin sections of archived paraffin material, staining with the antibody is highly sensitive and specific for AE [16]. Furthermore, this technique revealed an unknown feature of human AE that we called "small particles of E. multilocularis", i.e., spems [5,17,18].…”
Section: Immunohistological Findingsmentioning
confidence: 99%